1994
DOI: 10.1016/0014-5793(94)00647-4
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of monoclonal antibodies specific to multi‐ubiquitin chains of polyubiquitinated proteins

Abstract: Polyubiquitinated proteins tagged with multi-ubiquitin chains are substrates preferred by the 26 S proteasome (a ubiquitin/ATP-dependent proteolytic complex). Here, we developed a simple method for the efficient preparation of polyubiquitinated proteins which are degraded by the 26 S proteasome in an ATP-dependent manner. Our efficient method enabled us to produce ten monoclonal antibodies that recognized the multi-ubiquitin chains of the polyubiquitinated proteins, but not free ubiquitin or the protein moieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
212
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(222 citation statements)
references
References 43 publications
10
212
0
Order By: Relevance
“…The FK1 and FK2 antibodies specifically recognize ubiquitin-conjugated proteins, but not unconjugated ubiquitin (FK1 labels poly-ubiquitylated conjugates, FK2 labels mono-and poly-ubiquitylated proteins). 55,56 As shown in Figures 1b' and c', the immunoreactivity of FK1 and FK2 antibodies increases in prosβ2 mutant cells. We also find increased FK1 and FK2 labeling in Mov34 mutant cells (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 77%
“…The FK1 and FK2 antibodies specifically recognize ubiquitin-conjugated proteins, but not unconjugated ubiquitin (FK1 labels poly-ubiquitylated conjugates, FK2 labels mono-and poly-ubiquitylated proteins). 55,56 As shown in Figures 1b' and c', the immunoreactivity of FK1 and FK2 antibodies increases in prosβ2 mutant cells. We also find increased FK1 and FK2 labeling in Mov34 mutant cells (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 77%
“…It is involved in ERAD, wherein proteins are extracted from the ER, ubiquitinated, and then degraded by proteasomes (reviewed in Tsai et al, 2002). To analyze the disposition of ubiquitinated proteins in cells expressing p97(E578Q), we used an antibody that recognizes ubiquitin conjugates (Fujimuro et al, 1994; Figure 7A). This showed that expressing p97(E578Q) caused a significant build-up of ubiquitinated proteins on intracellular membranes.…”
Section: P97(e578q) Promotes Accumulation Of Ubiquitin Conjugates On mentioning
confidence: 99%
“…For this experiment, we used the FK2 antibody, which specifically detects ubiquitin moieties on cargo proteins (Fujimuro et al, 1994). When wild-type AMSH was expressed, only a marginal amount of ubiquitinated cargo was observed (Fig.…”
Section: Amsh Associates With the Escrt-iii Protein Chmp3mentioning
confidence: 99%